174 Sub-Coronal Inflatable Penile Prosthesis Placement: Patient Satisfaction and Outcomes. Issue 1 (1st April 2022) - Feng, C.; Langbo, W.; Anderson, L.; Cao, D.; Bajic, P.; Amarasekera, C.; Levine, L.
ABSTRACT: Introduction: Placement of an inflatable penile prosthesis (IPP) is a common surgical treatment of multiple disorders of male sexual function, including erectile dysfunction (ED) and Peyronie's disease (PD). The infra-pubic and peno-scrotal approaches have classically been favored for IPP placement since the first description of IPP placement in 1973 given reliably good outcomes. A sub-coronal incision was then described in 2016 for the implantation of a multicomponent IPP. The benefits of a sub-coronal approach to IPP placement includes exposure and access to the entire pendulous penis back to the mid bulb to allow for additional reconstructive procedures, such as plaque incision and grafting for Peyronie's disease, which previously would require an additional incision. Objective: Although the sub-coronal approach has been described to be operatively feasible with advantageous operating times, the aim of this project is to report outcomes of the sub-coronal approach, such as patient satisfaction, rate of revision, infection, and wound complications. Methods: A retrospective chart review from 5/11/2012 to 12/28/2020 was conducted on IPP placements performed at a single, tertiary-care institution to identify patients with IPPs placed via a sub-coronal approach. Data was collected at most recent follow-up date to determine outcomes measures such as satisfaction and complication rates. Results: Forty-six patients had IPPs placed through a sub-coronal incision. Mean time to follow-up was 9.81 months (0.46-45.6 months). Of these patients, 22 (47.8%) explicitly expressed satisfaction with the procedure at follow-up. Four (8.7%) had wound complications. Additionally, only one (2.2%) experienced a post-operative prosthetic infection. Revision was performed in 3 IPPs (6.5%). One revision was performed to primarily release prothesis tubing that had become adherent to the left base of penile shaft, which was causing patient discomfort. The same revision served additional cosmetic purpose to reduce redundant skin along the patient's circumcision line. The other two revisions were performed for prosthesis malfunctions: one prosthesis acquired "buckling" leading to a ventral curvature requiring release of scar contraction, and the other prosthesis developed a proximal aneurysm requiring removal and replacement. Conclusions: The sub-coronal approach for placement of an IPP is a promising alternative to the infra-pubic and peno-scrotal incisions with high patient satisfaction, low complication, and low revision rates. Disclosure: Any of the authors act as a consultant, employee or shareholder of an industry for: Boston Scientific and Coloplast